Manajemen Asuhan Keperawatan Pada Ny.M dengan Masalah Nyeri Akut Post Sectio Caesarea - Cholilatur Rohmania; Ati Surya Mediawati; Dyah Setyorini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the nursing management of acute pain problems in optimal one-day care in the Central Surgical Installation Room (IBS) RSUD using a 3M problem-based analysis (man, method, materials). The results of the research show that by carrying out optimal pain management, starting from assessment to evaluation of pain to optimizing non-pharmacological interventions (music therapy and deep breathing relaxation), patient pain complaints show improvement from moderate to mild scale (NRS) as well as the role of nurses in independent intervention also better. Problems studied in the room include the lack of optimal management of acute postoperative pain (from assessment to evaluation of pain, sometimes it is not done in the room), there is no SOP for pain intervention, there is no guideline for handling pain in the room, and the implementation of independent nurse intervention related to pain has not been implemented. In conclusion, with optimal assessment and evaluation of pain, including non-pharmacological technical interventions that are relatively easy to learn and apply independently by nurses, the results obtained are that the client's pain level is reduced from moderate pain on a scale of 5 to low pain on a scale of 3 on the NRS scale. Keywords: Central Surgical Installation, Nursing Care Management, Acute Pain